The Conditions for Obtaining Legal Gender Recognition: A Human Rights Evaluation - DUNNE, PETER ROBERT (Trinity College Dublin. School of Law. Discipline of Law, 2018)
This thesis evaluates how human rights law can impact the requirements which states impose as pre-conditions for legal gender recognition. At the international level ? within United Nations and regional human rights frameworks ? there is growing consensus that transgender persons should be formally acknowledged in their preferred gender. This movement towards gender recognition rights is now reinforced by domestic legal structures, with increasing (national law) possibilities for individuals to amend their gender status. Yet, while human rights have embraced a general entitlement to legal transitions, it is less clear how they can impact the processes by which transgender persons obtain formal acknowledgment. The thesis submits four ?conditions of recognition? to human rights review: (a) physical medical intervention; (b) compulsory divorce; (c) minimum age limits; and (d) mandatory binary gender. In focusing on these four categories, the thesis does not imply that they are the only possible prerequisites for gender recognition. There are numerous, additional conditions which can be (and have been) imposed on legal transition pathways. Rather, the thesis concentrates on the four selected requirements merely because, as a matter of both current and historical practice, they are the most common pre-conditions, which applicants for recognition confront. Throughout the substantive assessment undertaken, four human rights themes have particular relevance: (a) bodily integrity; (b) equality and non-discrimination; (c) marriage and family life; and (d) children?s rights. As with the categories of conditions, focusing on these four themes does not imply that they are the only rights applicable to legal transitions. The historical development of gender recognition illustrates that numerous rights intersect with transgender affirmation. This thesis concentrates on the four selected themes because, in the analysis which follows, they are the most relevant rights, cutting across various access requirements for formal acknowledgement. The thesis concludes that human rights law can significantly impact how states control acknowledgment of preferred gender. To the extent that many conditions of recognition ? imposed around the world ? violate core human rights standards, they should be removed as entry requirements for legal transitions. However, the thesis also notes the context-specific relationship between human rights and gender recognition. Given the comparative dearth of research on some transgender identities (e.g. transgender minors, non-binary persons.), the thesis acknowledges that the precise impact of human rights may ? at certain junctures ? not yet be clear. Involuntary medical requirements (e.g. surgery, sterilisation, etc.) are incompatible with bodily integrity guarantees. They constitute ?cruel and inhuman? and ?degrading? treatment. Depending upon the precise circumstances in which they are imposed, medical pre-conditions may even rise to the level of torture. Similarly, compulsory divorce is an unnecessary and disproportionate interference with marriage and family life. It is inconsistent with a transgender-inclusive human rights framework. There is growing consensus that absolutely excluding transgender minors from gender recognition does not serve the ?best interests of the child?. Young people should ? in accordance with their evolving capacities ? be affirmed in their preferred gender. However, while human rights principles (e.g. right of children to be heard.) can help define the contours of legal recognition for minors, the specific processes adopted must also have regard for key policy considerations, such as the difficulty of identifying ?persistent? transgender identities pre-puberty. On the emerging question of non-binary recognition, the thesis observes that there is no (current) human right to be acknowledged outside ?male? and ?female? categories. The thesis does, however, engage with the lived-experience of non-man and non-woman identities, and offers important insights on the continued sufficiency and practicality of dichotomous gender rules.
APPROVED
Keywords: Human Rights; Transgender; Family Law; Gender Identity; Equality